2020
DOI: 10.1093/ejcts/ezaa376
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to improve outcomes for acute type A aortic dissection with cerebral malperfusion

Abstract: OBJECTIVES We aimed to identify predictors of postoperative permanent neurological deficits (PNDs) and evaluate the early management of cerebral perfusion in patients undergoing surgical repair of acute type A aortic dissection with cerebral malperfusion. METHODS Between October 2009 and September 2018, a total of 197 patients with acute type A aortic dissection underwent aortic replacement. Of these, 42 (21.3%) patients had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 17 publications
0
31
0
Order By: Relevance
“…Furukawa et al reported that patients with partial or complete thrombosis of the arch vessels are at a high risk of cerebral malperfusion, especially when the false lumen of the innominate artery is occluded [9]. Gomibuchi et al stated that postoperative neurological deficiency is caused not only by disturbed blood flow in an occluded or stenotic carotid artery but also by a thromboembolism owing to thrombi derived from a thrombosed false lumen [6]. Gaul et al reported that in one-third of all patients with preoperative stroke, ischemic stroke was not caused by an extension of the dissection toward the supra-aortic vessels.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Furukawa et al reported that patients with partial or complete thrombosis of the arch vessels are at a high risk of cerebral malperfusion, especially when the false lumen of the innominate artery is occluded [9]. Gomibuchi et al stated that postoperative neurological deficiency is caused not only by disturbed blood flow in an occluded or stenotic carotid artery but also by a thromboembolism owing to thrombi derived from a thrombosed false lumen [6]. Gaul et al reported that in one-third of all patients with preoperative stroke, ischemic stroke was not caused by an extension of the dissection toward the supra-aortic vessels.…”
Section: Discussionmentioning
confidence: 99%
“…Once SCP is established, thrombi in the false lumen may enter the true lumen through a small entry. If re-entry occurrs at the distal site and we anastomose at the orifice of the brachiocephalic artery, it is possibile that the thrombi are transferred from the false lumen via the distal re-entry site [6].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations